An Analysis of the Role of the Family Environment in Supporting Early Reading Fluency among First-Grade Students at State Elementary School 7 Kediri, Tabanan - Putu Dian Handayani; Ida Bagus Putrayasa; Ni Ketut Desia Tristiantari (Jayapangus Press, 2026)
Early reading proficiency is one of the fundamental competencies that determines elementary school students’ academic success, as it serves as the foundation for understanding information, developing language skills, and participating effectively in learning activities across various subjects. However, difficulties in achieving fluent early reading remain a challenge for some elementary school students. One factor presumed to influence this condition is the family environment, which functions as the child’s first and primary educational setting. This study aims to analyze the role of the family environment in supporting the early reading fluency of elementary school students. The research employed a qualitative approach with a descriptive research design and was conducted among first-grade students at State Elementary School 7 Kediri. The research participants consisted of six parents, six students, and one classroom teacher, who were selected purposively based on their involvement in the early reading learning process. Data were collected through observation, in-depth interviews, and documentation and were subsequently analyzed using the stages of data reduction, data display, and conclusion drawing. The findings reveal that students’ early reading fluency is influenced not only by technical reading practice but also by the quality of family interactions. Parental assistance, educational communication, family literacy culture, and a conducive learning environment contribute significantly to enhancing students’ motivation, self-confidence, and reading fluency. The study also found that digital technology exerts varying effects on children’s reading habits. The use of digital media primarily for entertainment tends to reduce reading intensity, whereas the utilization of reading applications, educational videos, and digital storybooks accompanied by parental guidance can support the development of early reading skills. This study concludes that active family involvement through the establishment of a literacy culture, emotional support, educational communication, and the wise management of digital technology use constitutes a strategic factor in promoting the early reading fluency of elementary school students.